The northernmost record of Eriostethus rufus (Uchida, 1932) (Hymenoptera, Ichneumonidae) with an indication of new host, Trichonephila clavata (Koch, 1878) (Araneae, Araneidae) and its web manipulation - Takasuka, Keizo (Entomological Communications, 2021)
Eriostethus rufus (Uchida, 1932) is a polysphinctine ectoparasitoid of araneid spiders (Neoscona spp.) and is endemic to Japan. An individual was collected in Yamagata Prefecture (38º46' N), northern Japan, the northernmost record of the species and also the genus. Its identification was confirmed by morphology and by DNA barcoding. The cocoon was found in a large modified web, which is unique in that the web structure is shaped like an inverted triangle extending to over 50 cm with the cocoon hanging from an ill-defined part of the cocoon web without any organized structure surrounding the cocoon. The host spider of this individual appears to be Trichonephila clavata (Koch, 1878) (Araneidae, Nephilinae) based on several circumstantial evidences. The structure of the modified web suggests that the pre-existing web was partly reused, the orb web was completely removed, and sustaining threads of the barrier web would be newly moored to the substrates. This record means that E. rufus parasitises host spiders of two subfamilies, which is unusual for the group.